Communication—Car-Pooling and Regional Ridesharing Programs - Westerbeck, Gregory J.; Evans, James R. (Management Science, 1981)
Professors Leff (Management Science, Vol. 25, No. 8 (1979), p. 810) and Robinson (Management Science, Vol. 26, No. 4 (1980), pp. 433–434) have raised an interesting debate regarding car pool systems, algorithms, and human problems. Professor Leff sees the use of increasingly refined algorithms as the solution to forming carpools. Dr. Robinson, on the other hand, sees algorithms as the least part of a successful carpool system. In answer to Dr. Leff's query, algorithms are available to assist in ridesharing matching.